Публічні заклики до вчинення злочинних дій: лінгвістичний аналіз - Гапончук, В.; Haponchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті проаналізовано лінгвістичний аспект публічних закликів до вчинення злочинних дій. Проаналізовано 100 вироків за Єдиним державним реєстром судових рішень, в яких дії особи були кваліфіковані як публічні заклики до вчинення злочинних дій, досліджено відповідні висновки експертів (спеціалістів) відносно лінгвістичного аспекту публічних закликів. З аналізу лінгвістичної наукової літератури вбачається, що заклики до вчинення злочинних дій характеризуються наступними основними ознаками: 1) це мовленнєвий акт; 2) це форма спонукання; 3) це директивне мовлення; 4) метою публічних закликів є спонукання виконати певну дію або сукупність дій; 5) публічні заклики містять три елементи: відправник (той, хто надсилає повідомлення, адресант, суб’єкт дії), саме повідомлення (інформація, дії) та отримувач (той, хто його сприймає, адресат, об’єкт дії). The article analyzes the linguistic aspect of public appeals for committing criminal acts. The key findings of the study are based on the in-depth analysis of 100 court sentences under the Unified State Register of Court Decisions, in which the actions of the person were qualified as public appeals for committing criminal acts, including the corresponding conclusions of the experts concerning the linguistic aspect of such appeals. The emphasis is laid on the linguistic features, which should be cosidered as markers of public appeals to commit criminal acts. The linguistic analysis of the relevant statements, texts, visual aids is carried out by utilizing special knowledge in criminal proceedings which are crucial to determine properly whether there was a public incitement to commit criminal act or not. Linguistic scientific literature states that appeals for committing criminal acts are characterized by the following features: 1) this is a speech act; 2) this is a form of incitement; 3) it is a direct order; 4) the purpose of public appeal is to prompt a certain action or set of actions. Public appeals contain three components: the sender (sender, addressee, subject of action), the message (information, actions) and the recipient (the one who receives it, the addressed, object of action). Appeals can be direct and indirect.
Public Incitement to Commit Criminal Acts: Linguistic Analysis
Keywords: публічні заклики; мовленнєвий акт; мовна агресія; спонукання; лінгвістика; текст; public appeals; speech act; linguistic aggression; induction; linguistics; text